2007
DOI: 10.1144/sp293.15
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of mantle sections beneath Yakutian kimberlite pipes using monomineral thermobarometry

Abstract: Four original monomineral methods for mantle peridotite associations are used to reconstruct P–T conditions beneath the kimberlite pipes of Yakutia. The clinopyroxene Jd–Di method gives the closest coincidence with Opx barometry in accord with all physico-chemical boundaries. Garnet thermometers calibrated using Opx, Gar–Cpx and Ni-garnet thermometers and two variants of barometers were developed separately for pyroxenites and peridotites. A Cr–Sp thermobarometer uses the monomineralic version of the Ol–Sp the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Previous studies on the lateral and vertical variations of the mantle structure of Siberian platform have shown that a layering exists in the SCLM beneath Udachnaya and other Siberian kimberlite pipes (Ashchepkov et al, 2010;Ashchepkov et al, 2008a;Boyd et al, 1997;Griffin et al, 2005;Griffin et al, 1999b;Nimis et al, 2009). For example, the garnets from kimberlite heavy mineral separates show an increasing depletion of the lower part of the mantle lithosphere northward (Griffin et al, 1999b).…”
Section: Geological Backgroundmentioning
confidence: 96%
“…Previous studies on the lateral and vertical variations of the mantle structure of Siberian platform have shown that a layering exists in the SCLM beneath Udachnaya and other Siberian kimberlite pipes (Ashchepkov et al, 2010;Ashchepkov et al, 2008a;Boyd et al, 1997;Griffin et al, 2005;Griffin et al, 1999b;Nimis et al, 2009). For example, the garnets from kimberlite heavy mineral separates show an increasing depletion of the lower part of the mantle lithosphere northward (Griffin et al, 1999b).…”
Section: Geological Backgroundmentioning
confidence: 96%
“…Single-mineral thermometer-barometer pairs, such as those available for peridotitic garnet and clinopyroxene (Ryan et al 1996;Nimis and Taylor 2000;Grütter et al 2006), permit thermobarometric surveys to extend across copious data for mantlederived xenocrysts. Although with some limitations concerning their reliability and applicability (e.g., Cookenboo and Grütter 2010), the single-mineral methods have enabled the vertical and horizontal mapping of the lithospheric mantle to an extent far beyond that achievable with xenoliths alone (e.g., Griffin et al 1999Griffin et al , 2002Griffin et al , 2004Malkovets et al 2007;Ashchepkov et al 2008;Grütter and Tuer 2009;Lehtonen et al 2009;Nimis et al 2009;Zozulya et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We have calculated and estimated the P-T parameters with the help of an olivine-spinel (Ol-Sp) geothermometer, provided in [88]. The oxygen fugacity was determined using an Ol-Sp oxybarometer, provided in [89], in accordance with oxybarometers [90,91]. For the chrome spinels I group (high Al′), the calculated temperatures of the Ol-Sp equilibrium are TOl-Sp = 1020-920 °C, and fO2 = (−0.7)-(−1.5) (Table 1); for the chrome spinels II group (medium-, low-Al′), the calculated temperatures are TOl-Sp = 891-1003 °C , and fO2 = (−1.1) − (−4.4); for the chrome spinels III group, these values are TOl-Sp = 846-…”
Section: Spinel and Olivine Geothermometers And Olivine-spinel Oxybarometersmentioning
confidence: 99%